Smoking Behaviour and Its Impact on the Quality of Life of the Beneficiary Families of Social Assistance Funds in East Java, Indonesia - Nurhasana, Renny; Ratih, Suci Puspita; Gayatri, Rara Warih; Tama, Tika Dwi; Shellasih, Ni Made; Satrya, Aryana; Ningtyas, Fadhilah Rizky; Muhafilah, Nurul (UI Scholars Hub, 2023)
The government implements social assistance programs for poor families and vulnerable groups. Therefore, the implementation is still facing various challenges. One of the toughest challenges is smoking behaviour. As the income has been increasing, the cigarette’s expense is also high. Cigarette’s expenditure substitutes other basic needs, such as nutritional foods, health, and education expenses. This study analyses smoking behaviour in social assistance recipients and its impact on quality of life. By using qualitative method, particularly the Rapid Assessment Procedure, data were obtained through in-depth interviews. The study uses purposive method to collect samples in East Java, both Malang City and Kediri Regency. Results show that all the informants have family members who were heavy smokers. The daily cigarette’s expenditure of social assistance’s recipients was significant compared to their daily expenses. It substitutes basic needs expenses and affects their quality of life specifically for nutritional, health, and child’s education status. Furthermore, due to nicotine addiction, it is very difficult for smokers to reduce the number of cigarette consumption, even though at difficult economies. Smoking behaviour also leads to family conflicts. It is important to regulate social assistance recipients who still disburse their budget for temptation goods such as cigarette. In addition, government must inform the negative impacts of smoking, as well as promote the healthy life behaviour using the existing program, Family Capacity Building Meeting/Pertemuan Peningkatan Kemampuan Keluarga (P2K2). As part of effective solutions to reduce smoking prevalence, unaffordable cigarette price is important due to lowering the consumption of addictive product.